Hypersensitivity pneumonitis - Lacasse, Yves; Cormier, Yvon (Orphanet journal of rare diseases, 2006)
Hypersensitivity pneumonitis (HP) is a pulmonary disease with symptoms of dyspnea and cough resulting from the inhalation of an antigen to which the subject has been previously sensitized. The incidence of HP is unknown. A population-based study estimated the annual incidence of interstitial lung diseases as 30:100,000 and HP accounted for less than 2% of these cases. The diagnosis of HP can often be made or rejected with confidence, especially in areas of high or low prevalence respectively, using simple diagnostic criteria. Chest X-rays may be normal in active HP; High Resolution Computed Tomography is sensitive but not specific for the diagnosis of HP. The primary use of pulmonary function tests is to determine the physiologic abnormalities and the associated impairment. Despite the pitfalls of false positive and false negatives, antigen-specific IgG antibodies analysis can be useful as supportive evidence for HP. Bronchoalveolar lavage plays an important role in the investigation of patients suspected of having HP. A normal number of lymphocytes rules out all but residual disease. Surgical lung biopsy should be reserved for rare cases with puzzling clinical presentation or for verification the clinical diagnosis when the clinical course or response to therapy is unusual. Being an immune reaction in the lung, the most obvious treatment of HP is avoidance of contact with the offending antigen. Systemic corticosteroids represent the only reliable pharmacologic treatment of HP but do not alter the long-term outcome. The use of inhaled steroids is anecdotal. Treatment of chronic or residual disease is supportive.